Municipal finances: analysis of the public spending of the sinaloa municipality (2010-2015) and its impact on poverty indicators (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2019)
Two main aspects emerged from the main objective of this investigation, to analyze the behavior of the amounts spent by the 18 Sinaloa State Councils in the period 2010 to 2015 and their impact on a poverty indicator shown by CONEVAL and to identify the degree of perception about the expenditure classification made by the Local Governments (GL) in the analysis period. As a result, an econometric model was designed that determined the correlation between each of the spending categories (X) and the Social Lag Index (Y). Likewise, 70.43 percent dogmatized that they disagree and totally disagree about the amount of resources allocated to current spending; 82.9% indicated lack of transparency in resource management; 80 percent that the distribution has not been fair and at the same time that they have not had an impact on fighting poverty. The type of research took up the quantitative, non-experimental, cross-sectional and descriptive approach through the application of a survey to a random probabilistic sample of 112 inhabitants using ICTs.
Keywords: public spending; social backwardness index; municipal governments